2017
DOI: 10.1002/gps.4767
|View full text |Cite|
|
Sign up to set email alerts
|

Aspirin and incident depressive symptoms: A longitudinal cohort study over 8 years

Abstract: Our study found that prescription of aspirin offered no significant protection against incident depressive symptoms. Whether aspirin is beneficial in a subgroup of depression with high levels of inflammation remains to be investigated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 39 publications
0
24
1
Order By: Relevance
“…Epidemiological studies suggest that people taking aspirin or statins might be less likely to have concurrent depression [26][27][28][29][30], although the evidence is inconsistent, with some negative reports [31]. While there are positive randomised controlled trials of statins for the treatment of depression [32][33][34], and meta-analytic evidence for their effectiveness [35], no studies have investigated their therapeutic potential among youth.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies suggest that people taking aspirin or statins might be less likely to have concurrent depression [26][27][28][29][30], although the evidence is inconsistent, with some negative reports [31]. While there are positive randomised controlled trials of statins for the treatment of depression [32][33][34], and meta-analytic evidence for their effectiveness [35], no studies have investigated their therapeutic potential among youth.…”
Section: Introductionmentioning
confidence: 99%
“…Using a random-effects model, the pooled HR of the three cohort studies [14,17,21] was 0.624 (95% CI: 0.0503 to 1.198, p = 0.033), supporting a reduced risk of depression with ASA exposure. The high heterogeneity (I 2 = 79.25%), as seen in Figure 2, could be due to the different population characteristics studied (e.g., patients being at different phases of illness, of differing demographics, and on different treatments).…”
Section: Resultsmentioning
confidence: 95%
“…The salient details of the studies are summarized in Table 1. There were two randomized, placebo-controlled, double-blind trials and two key cohort studies (the Geelong Osteoporosis Study [14] and the Osteoarthritis Initiative (OAI) study [17]). A meta-analysis was limited due to the small number of studies and dissimilar study designs and outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 56 027 cases of depression were investigated in this meta‐analysis. For the ascertainment of depression, four studies 12,18,19,25 used self‐reported measures of depression, three studies 17,20,22 used the Structured Interview for the Diagnostic and Statistical Manual of Mental Disorders, fourth edition, three studies 21,23,26 used the International Classification of Disease, 10th revision, one study 24 used hospital contact with depression or filled prescriptions for antidepressant medication, and one study 27 used self‐report of a medical diagnosis of depression or the use of antidepressants.…”
Section: Resultsmentioning
confidence: 99%
“…As for the ascertainment of aspirin use, eight articles 12,17‐20,25,27 used self‐report questionnaires and the other four studies conducted in Denmark 21,23,24,26 used objective assessment tools such as the Danish Prescription Registry Anatomical Therapeutic Chemical (ATC) codes. Regarding the duration of aspirin use, the average duration of aspirin use was ≥5 years in nine articles 12,17,20,21,23‐27 . In one study, 18 the average duration of aspirin use was ≥2 years.…”
Section: Resultsmentioning
confidence: 99%